Heparin attenuates symptoms and mast cell degranulation induced by AMP nasal provocation - Zeng, Dewan; Prosperini, Gaetano; Russo, Cristina; Spicuzza, Lucia; Cacciola, Rosella R; Di Maria, Guiseppe U; Polosa, Riccardo (Journal of allergy and clinical immunology, 2004)
Previous studies have shown that inhaled heparin attenuated the airway responses to allergen, exercise, and AMP bronchial provocation, possibly through an inhibition of mast cell activation. The aim of this study was to provide the evidence of in vivo inhibition of human mast cell activation by heparin in a noninvasive model. Nine atopic and 6 nonatopic subjects received placebo and unfractionated heparin sodium (5000 IU/mL) 15 minutes before an AMP nasal provocation in a double-blind crossover study design. The nasal lavage was collected from these subjects before or 3, 5, 15, or 30 minutes after the AMP nasal challenge, and concentrations of histamine and tryptase in the nasal lavage were measured. AMP nasal provocation produced considerable sneezing and induced a transient increase in histamine and tryptase release, with peak values achieved at 3 to 5 minutes after the challenge in all atopic subjects. Compared with placebo, inhaled heparin significantly attenuated the release of histamine and tryptase induced by AMP challenge ( P = .012 and .004, respectively). Moreover, the AMP-induced sneezing was also inhibited by pretreatment with heparin ( P = .016). In nonatopic subjects, AMP did not induce a significant increase in histamine and tryptase release on placebo-treated or heparin-treated days. These data suggest that AMP nasal provocation and AMP bronchial provocation cause mast cell mediator release in a similar fashion. In addition, the data support the hypothesis that inhaled heparin plays a protective role against AMP provocation by inhibition of mast cell activation.